Analisis Penggunaan Dana Alokasi Umum Tambahan Dalam Program Pemberdayaan Masyarakat Di Dinas Pemberdayaan Masyarakat Dan Kalurahan Kabupaten Bantul - Fatharani, Femi; Mutiara Hapsari, Cinthia (JMMU: JURNAL MAHASISWA MANAJEMEN DAN UMUM, 2026)
The use of Additional General Allocation Funds (DAU-T) has a significant impact on community welfare and regional development, so the use of these funds is very important for the surrounding community and is very helpful for the community, such as infrastructure development, for example, the construction of bridges or roads makes it easier for people to earn a living and socialize with other villages. This study aims to determine the use of Additional General Allocation Funds (DAU-T) in community empowerment programs in 2024 in Bantul Regency and to determine the effectiveness of the use of Additional General Allocation Funds (DAU-T) in community empowerment programs based on infrastructure development. The research method used by researchers is an empirical qualitative approach, the type of research used is field research and case studies. The data collection techniques are interviews and documentation. The analysis techniques used are data reduction, data presentation, verification and drawing conclusions. The results of the study show that: The use of Additional General Allocation Funds (DAU-T) in Bantul Regency includes physical and non-physical development, from these activities that the use of Additional General Allocation Funds is mostly used for physical programs only while non-physical is still lacking. The effectiveness of the use of Additional General Allocation Funds (DAU-T) in community empowerment programs based on infrastructure development has not been effective due to the management of Additional General Allocation Funds (DAU-T) in community empowerment programs based on infrastructure development has not been effective due to the management of Additional General Allocation Funds (DAU-T) in Bantul Regency. The Additional General Allocation Fund (DAU-T) funding assistance in the Village is hampered by a lack of Human Resources (HR), numerous misappropriations of development funds, and poor management. Keywords: Analysis, Management, Additional General Allocation Fund, Community Empowerment.